Influence of dorsiflexion shoes on neuromuscular fatigue of the plantar flexors after combined tapping-jumping exercises in volleyball players - Lapole, T.; Ahmaidi, S.; Gaillien, B.; Lepretre, P.-M. (The Journal of Strength and Conditioning Research, 2013)
Dorsiflexion shoes could be useful to increase jumping performance. The aim of the present study was to investigate the impact of wearing shoes inducing moderate dorsiflexion (2°) on neuromuscular fatigue induced by volleyball exercises involving multiple stretch-shortening cycles. Squat jump (SJ) and countermovement jump (CMJ) performance, and plantar flexors isometric voluntary and evoked contractile properties were assessed in 10 unfamiliarized trained volleyball players before and after a 10-minute intensive combined tapping-jumping volleyball exercise performed, in blinded randomized conditions, with neutral (0°) or moderate dorsiflexion (2°). No significant difference was observed on SJ performance in neutral and moderate dorsiflexion conditions. However, CMJ height was initially lower with 2° dorsiflexion compared with 0° (p < 0.05). Height in CMJ was increased after exercise with 2° dorsiflexion shoes and remained unchanged in neutral 0° condition. Combined tapping-jumping volleyball exercise also induced a significant decrease in maximal voluntary contraction (p < 0.001), peak-twitch torque (p = 0.009), contraction time (p < 0.001) and twitch relaxation rate (p = 0.001) values without any significant difference between neutral and dorsiflexion conditions. Voluntary activation level (p = 0.014) and rate of force development (p = 0.05) were also decreased in both conditions. In conclusion, acute moderate dorsiflexion had no effect on jumping performance and neuromuscular fatigue in unfamiliarized trained subjects and altered the elastic energy store in plyometric condition (CMJ). Future studies are necessary to investigate the chronic effect of moderate dorsiflexion on jumping performance and neuromuscular fatigue in trained volleyball players.